OPTIMALISASI KETERAMPILAN PERTOLONGAN PERTAMA CEDERA OTOT MENGGUNAKAN METODE REST, ICE, COMPRESS AND ELEVATE (RICE MANAGEMENT) - Fitriana, Nurul Fatwati; Ratna Estria, Suci; Hakim Nitiprodjo, Abdul; Riskiyani Dwi Nandia, Jumiati; Ratna Juwita, Dina; Dwi Aprilina, Happy; Dhiah Anggraeni, Atika; Andodo, Candra; Leona Amelia, Vivi; Suparti, Sri (Universitas Kadiri, 2023)
Injuries can occur anytime and anywhere and can be experienced by anyone. Common types of injuries that occur in daily life are muscle injuries, such as sprains, fractures, dislocations, and bruises. Muscle injuries that are not promptly and correctly treated can result in complications and disrupt daily activities. The management of muscle injuries involves the RICE Management approach, which includes rest, applying cold compresses, compression, and elevating the injured area. Community service is carried out through lectures and simulations on RICE Management. This activity was attended by 32 participants, consisting of health volunteers. During the implementation, participants were cooperative and able to explain the definition, signs and symptoms, complications, and practice the management of muscle injuries using RICE Management.